Mammalian mRNA Splice-Isoform Selection Is Tightly Controlled - Chisa, Jennifer L. (Copyright © 2007 by the Genetics Society of America, 2007)
Post-transcriptional RNA processing is an important regulatory control mechanism for determining the phenotype of eukaryotic cells. The processing of a transcribed RNA species into alternative splice isoforms yields products that can perform different functions. Each type of cell in a multi-cellular organism is presumed to actively control the relative quantities of alternative splice isoforms. In this study, the alternatively spliced isoforms of five mRNA transcription units were examined by quantitative reverse transcription–PCR amplification. We show that interindividual variation in splice-isoform selection is very highly constrained when measured in a large population of genetically diverse mice (i.e., full siblings; N = 150). Remarkably, splice-isoform ratios are among the most invariant phenotypes measured in this population and are confirmed in a second, genetically distinct population. In addition, the patterns of splice-isoform selection show tissue-specific and age-related changes. We propose that splice-isoform selection is exceptionally robust to genetic and environmental variability and may provide a control point for cellular homeostasis. As a consequence, splice-isoform ratios may be useful as a practical quantitative measure of the physiological status of cells and tissues.